HUBUNGAN TINGKAT PENDIDIKAN, PENGETAHUAN, DAN DUKUNGAN KELUARGA DENGAN KEPATUHAN KONSUMSI MULTI-MICRONUTRIENT SUPPLEMENT (MMS) PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS LABAKKANG: THE RELATIONSHIP BETWEEN LEVEL OF EDUCATION, KNOWLEDGE, AND FAMILY SUPPORT WITH COMPLIANCE IN CONSUMING MULTI-MICRONUTRIENT SUPPLEMENTS (MMS) AMONG PREGNANT WOMEN IN THE WORKING AREA OF LABAKKANG PUBLIC HEALTH CENTER - Hamzah, Alya Rohana Pratiwi; Amir, Safrullah; Hasan, Nurzakiah; Najamuddin, Ulfah; Fajarwati Ibnu, Indra (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2025)
Introduction. In overcoming micronutrient deficiencies in pregnant women, WHO in updating the 2020 Antenatal Care (ANC) guidelines recommends providing Multi-Micronutrient Supplement (MMS) to replace Iron Folid Acid Tablets (IFA). However, compliance with MMS consumption in pregnant women is still low. Level of education, knowledge, and family support are factors that influence the compliance of pregnant women in consuming MMS. Aim. To determine the relationship between education level, knowledge, and family support with compliance with MMS consumption in pregnant women in the Labakkang Health Center work area. Method. This study is an analytical observational study using a cross-sectional design. Samples were obtained using a total sampling technique of 96 pregnant women. The research instrument used a questionnaire on compliance, knowledge, and family support. Data analysis used the chi-square test. Results. Based on the results of the study, the majority of pregnant women were highly educated (62.5%) and had good knowledge (67.7%), lack of family support for pregnant women (68.8%), and were not compliant in consuming MMS (58.3%). After statistical tests were conducted, the results showed a significant relationship between education level and compliance with MMS consumption (p-value = 0.000), knowledge with compliance with MMS consumption (p-value = 0.009), and family support with compliance with MMS consumption (p-value = 0.004). Conclusion and Suggestions. Compliance of pregnant women in consuming MMS is still relatively low and there is a relationship between education level, knowledge, and family support with compliance with MMS consumption in pregnant women in the Labakkang Health Center work area. Therefore, to increase compliance with MMS consumption, it is recommended for families to remind pregnant women to consume MMS by collaborating with health workers to obtain education regarding the importance of MMS.